Curative Surgical Resection of Adrenocortical Carcinoma: Determining Long-term Outcome Based on Conditional Disease-free Probability. Issue 1 (January 2017) - Kim, Yuhree; Margonis, Georgios A.; Prescott, Jason D.; Tran, Thuy B.; Postlewait, Lauren M.; Maithel, Shishir K.; Wang, Tracy S.; Glenn, Jason A.; Hatzaras, Ioannis; Shenoy, Rivfka; Phay, John E.; Keplinger, Kara; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To evaluate conditional disease-free survival (CDFS) for patients who underwent curative intent surgery for adrenocortical carcinoma (ACC). Background: ACC is a rare but aggressive tumor. Survival estimates are usually reported as survival from the time of surgery. CDFS estimates may be more clinically relevant by accounting for the changing likelihood of disease-free survival (DFS) according to time elapsed after surgery. Methods: CDFS was assessed using a multi-institutional cohort of patients. Cox proportional hazards models were used to evaluate factors associated with DFS. Three-year CDFS (CDFS3 ) estimates at "x" year after surgery were calculated as follows: CDFS3  = DFS(x+3) /DFS(x) . Results: One hundred ninety-two patients were included in the study cohort; median patient age was 52 years. On presentation, 36% of patients had a functional tumor and median size was 11.5 cm. Most patients underwent R0 resection (75%) and 9% had N1 disease. Overall 1-, 3-, and 5-year DFS was 59%, 34%, and 22%, respectively. Using CDFS estimates, the probability of remaining disease free for an additional 3 years given that the patient had survived without disease at 1, 3, and 5 years, was 43%, 53%, and 70%, respectively. Patients with less favorable prognosis at baseline demonstrated the greatest increase in CDFS3 over time (eg, capsular invasion: 28%–88%, Δ60% vs no capsular invasion: 51%–87%, Δ36%). Conclusions: DFS estimates for patients with ACC improved dramatically over time, in particular among patients with initial worse prognoses. CDFS estimates may provide more clinically relevant information about the changing likelihood of DFS over time.